Interactive math comics: An analysis of Indonesian and Spanish students’ responses - Marhaeni, Nafida Hetty; Arnal-Palacián, Mónica; Irfan, Muhammad (Jurnal Infinity, 2025)
This study investigates the responses of Indonesian and Spanish students to the use of interactive mathematics comics in their education. The research aims to see the practicality of these comics on student engagement, comprehension, and retention of mathematical concepts across different cultural contexts. Using a quantitative approach, the study analyzes data through normality and homogeneity tests to ensure the reliability and consistency of responses. Results show that Indonesian and Spanish students respond positively to interactive mathematics comics, demonstrating increased motivation and interest. However, cultural differences significantly influence the perception of specific indicators such as content quality, technical quality, and language usage. Indonesian students, who are generally accustomed to traditional teaching methods, found the comics engaging and helpful in understanding complex concepts. On the other hand, Spanish students, who are more familiar with interactive and student-centered learning, showed mixed responses depending on their educational experiences and expectations. Despite these differences, both groups recognized the value of interactive comics as a supplementary educational tool. Future research could explore a larger and more diverse sample size, including longitudinal studies to assess the sustained impact of such tools and further investigate the integration of other multimedia elements like augmented reality to enhance interactivity. From these results, the Mathematics Comic on Cartesian coordinates material developed is practical and can be used in mathematics learning. This is because the Mathematics Comic on Cartesian coordinates material received a good response, and students hope that learning mathematics will be more fun and effective.